Grace Under Pressure: Resiliency of Quality Monitoring of Stroke Care During the Covid-19 Pandemic in Mexico City - Medina-Rioja, Raul; González-Calderón, Gina; Saldívar-Dávila, Sergio; Estrada Saúl, Alexander; Gayón-Lombardo, Erika; Somerville-Briones, Nicole; Calleja-Castillo, Juan Manuel (Frontiers in Neurology, 2022)
Stroke is one of the leading causes of death among adults worldwide. The World Health Organization (WHO) officially declared a COVID-19 pandemic on March 11, 2020.The first case in Mexico was confirmed on February 28, 2020, subsequently becoming one of the countries most affected by the pandemic. In this paper, we aim to describe changes in the demand for stroke healthcare assistance at the National Institute of Neurology and Neurosurgery during the pandemic. For this study, we analyzed data for acute stroke patients registered in the RES-Q platform, during 2019 and 2020. A total of 135 acute stroke patients were enrolled in this registry. For patients in the year prior to the pandemic and during the pandemic year, patients were studied similarly (with NCCT, CTA, MRA, DSA or more frequently (early carotid imaging, Holter monitoring). Treatment for secondary prevention (antihypertensives, antiplatelets, statins) did not differ. Frequency of NIHSS scale at arrival and early dysphagia test improved. Regarding reperfusion treatment, the proportion of patients treated with IV thrombolysis increased from 21 to 42%, a high percentage of thrombolyzed stroke patients by international standards. Door to needle time decreased non significantly. An increase in the delay in reaching the hospital from the onset of stroke symptoms of >1 hour was observed. The aforementioned stroke protocol and quality monitoring system, as well as In the National Institute of Neurology and Neurosurgery, acute stroke treatment has continued to gradually improve, a process that was not thwarted during the COVID-19 pandemic after the implementation of a quality monitoring registry.